2021
DOI: 10.1093/plphys/kiab377
|View full text |Cite
|
Sign up to set email alerts
|

HECATE2 acts with GLABROUS3 and Tu to boost cytokinin biosynthesis and regulate cucumber fruit wart formation

Abstract: Warty fruit in cucumber (Cucumis sativus L.) is an important quality trait that greatly affects fruit appearance and market value. The cucumber wart consists of fruit trichomes (spines) and underlying tubercules, in which the existence of spines is prerequisite for tubercule formation. Although several regulators have been reported to mediate spine or tubercule formation, the direct link between spine and tubercule development remains unknown. Here, we found that the basic Helix-Loop-Helix (bHLH) gene HECATE2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Previous studies indicated that the ethylene, auxin, cytokinin and gibberellin signaling pathways are involved in cucumber spine formation (Che & Zhang, 2019; Wang et al ., 2021; Zhang et al ., 2021). Thus, we measured the level of endogenous gibberellic acid (GA3), auxin (indole‐3‐acetic acid, IAA; indole‐3‐butytric acid, IBA), cytokinin (isopentenyl adenosine, IPA; trans‐zeatin riboside, TZR), and ethylene in the ovary of L‐SB and S‐SB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies indicated that the ethylene, auxin, cytokinin and gibberellin signaling pathways are involved in cucumber spine formation (Che & Zhang, 2019; Wang et al ., 2021; Zhang et al ., 2021). Thus, we measured the level of endogenous gibberellic acid (GA3), auxin (indole‐3‐acetic acid, IAA; indole‐3‐butytric acid, IBA), cytokinin (isopentenyl adenosine, IPA; trans‐zeatin riboside, TZR), and ethylene in the ovary of L‐SB and S‐SB.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the level of endogenous gibberellic acid, auxin, and cytokinin, 1 g of ovary samples at 2 DBA from L‐SB and S‐SB were frozen in liquid nitrogen. The extraction and quantification of phytohormones were performed using high‐performance liquid chromatography electrospray ionization tandem mass spectrometry (HPLC‐ESI‐MS/MS) as previously described (Wang et al ., 2021). Ethylene release rate of ovary samples at 5 DPP was measured as previously described (Zhang et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, one NS candidate gene, encoding an auxin transport protein, was identified by genome‐wide association study (GWAS). Recently, the powerful biotechnology CRISPR/Cas9 has been applied in the improvement of cucumber agronomic traits (Chandrasekaran et al., 2016; Hu et al., 2017; Wang et al., 2021; Xin et al., 2019; Yang et al., 2020; Zhang et al., 2020; Zhang, Li, et al., 2021). We here demonstrate that the knockout ns mutant generated by CRISPR/Cas9 display the numerous fruit spine phenotype.…”
Section: Introductionmentioning
confidence: 99%